Transsexualism, homosexuality, and priesthood: canonical remarks concerning the relevant ratio fundamentalis institutionis sacerdotalis standards = La transsexualité et l’homosexualité face à la prêtrise : Remarques juridico-canoniques concernant les normes Ratio Fundamentalis Institutionis Sacerdotalis = Transessualità, omosessualità e sacerdozio : Osservazioni giuridico-canoniche riguardanti le norme Ratio Fundamentalis Institutionis Sacerdotalis - Pastwa, Andrzej (Philosophy & canon law, 2018)
The scientific contemplation, inspired by the publication of the new Ratio Fundamentalis, is concentrated around the following issues: (1) accepting/not accepting to seminar, accepting/not accepting a transsexual person to the holy orders, (2) letting/not letting a homosexual person to the holy orders. Two assumptions accompany the detailed exploration of these issues. Firstly, what is key for achieving reliable research results is the affirmation of the appropriate anthropology, according to which both transsexualism and homosexuality are to be treated under common denominator as psychosexual disorders. Secondly, if the context closer to the research is defined by a doctrinal background, drafted for each of the mentioned phenomena, in the form of relevant anthropological and ethical, as well as theological and ecclesiological principles and guidelines included in numerous sources of the Church’s Magisterium, then with reference to both transsexualism and homosexuality, an invaluable cognitive character is presented by especially one source document, namely the Instruction of the 2015 Congregation for Catholic Education.